1993
DOI: 10.1523/jneurosci.13-03-01227.1993
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial versus visuomotor activity in the premotor and prefrontal cortex of a primate

Abstract: We thank Mr. William Burriss for his assistance. We also thank Dr. Eilon Vaadia for his critical reading of the manuscript. G.dP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
147
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(161 citation statements)
references
References 79 publications
13
147
1
Order By: Relevance
“…K. Miller, Li, & Desimone, 1993). Such disruption is not seen in delayresponsive dPFC cells (di Pellegrino & Wise, 1993a, 1993bE. K. Miller et al, 1996).…”
Section: Nonhuman Primate Researchmentioning
confidence: 74%
“…K. Miller, Li, & Desimone, 1993). Such disruption is not seen in delayresponsive dPFC cells (di Pellegrino & Wise, 1993a, 1993bE. K. Miller et al, 1996).…”
Section: Nonhuman Primate Researchmentioning
confidence: 74%
“…On one hand, several characteristics of dynamic activation patterns in our model reflect processes that have been linked to different cortical areas. For instance, the selfsustaining working memory peaks discussed here can survive intervening presentations of stimuli, a characteristic of spatial representations in dorso-lateral prefrontal cortex (di Pellegrino & Wise, 1993). By contrast, although activation patterns in our perceptual field can be sustained under some conditions (see the generation of a "different" response in Fig.…”
Section: The Dft Is Grounded By Neural Principlesmentioning
confidence: 80%
“…For instance, it is likely that the development of the dorso-lateral prefrontal cortex plays a central role in the tasks we discuss because this region of cortex is heavily involved in the on-line maintenance of spatial information (Awh, et al, 1999;di Pellegrino & Wise, 1993;Kessels, Postma, Wijnalda & de Haan, 2000;Nelson, et al, 2000). Moreover, the development of the prefrontal cortex shows a protracted course that continues into the postadolescent years (Gogtay, et al, 2004;Rakic, 1995;Sowell, Thompson, Tessner & Toga, 2001).…”
Section: Development In the Dftmentioning
confidence: 99%
See 1 more Smart Citation
“…Andersen and colleagues demonstrated that signals in parietal cortex of monkeys could provide a command that signaled upcoming movement intent for specific movement directions and expected reward value (Musallam et al, 2004). Large extents of frontal cortex outside of MI are active in movement planning (Kurata & Wise, 1988;Fu et al, 1995;Toni et al, 1999;Crammond & Kalaska, 2000;Harrington et al, 2000) and movement intent (di Pellegrino & Wise, 1993;Rao, et al, 1997;Kalaska & Crammond, 1995;Crammond & Kalaska, 2000), suggesting that useful movement signals may be available in these areas as well. Indeed, premotor and primary motor areas in the monkey provide different types of movement information .…”
Section: Introductionmentioning
confidence: 99%